Up-regulation of cyclooxygenase-2-derived prostaglandin E(2) in colon cancer cells resistant to 5-fluorouracil - Choi, Cheol Hee (The Korean Surgical Society, 2011)
PURPOSE: It has been suggested that constitutive up-regulation of cyclooxygenase (COX)-2 is associated with resistance to apoptosis, increased angiogenesis, and increased tumor invasiveness in various cancers including colon cancer. There are many factors involved in the resistance to 5-fluorouracil (5-FU) in colon cancer. However, little is known about the role of COX-2 in acquired resistance to 5-FU in colon cancer. METHODS: Hence we investigated whether COX-2 contribute to acquired resistance to 5-FU in colon cancer cells, using cytotoxicity assay for cell survival, reverse transcription-polymerase chain reaction (RT-PCR) for vascular endothelial growth factor (VEGF), quantitative RT-PCR for COX-1 and COX-2, and enzyme-linked immunosorbent assay for PGE(2). RESULTS: The 5-FU resistant colon cancer cells, SNU-C5/5FUR, showed increased expression of COX-2, prostaglandin E(2) (PGE(2)), and VEGF, compared to its parental cell (SNU-C5). By treatment with meloxicam, the expression of PGE(2) and VEGF was reduced significantly in the resistant cells, but not in the parent cells. CONCLUSION: These results demonstrate that COX-2 derived PGE(2) is up-regulated and COX-2 inhibitor may have an anti-angiogenic effect in the colon cancer cells resistant to 5-FU.